Review about Organic-Inorganic Perovskite Single Crystal : Synthesis Methods, Properties and Applications - Monik N. Maisuriya; Priyanka Desai (International Journal of Scientific Research in Science and Technology, 2024)
Due to their easy synthesis and exceptional optoelectronic characteristics, such as their long carrier diffusion length, high carrier mobility, low trap density, and tuneable absorption edge ranging from ultraviolet (UV) to near-infrared (NIR), perovskite single crystals have attracted a lot of attention in recent years. These properties have the potential to be used in solar cells, photo-detectors (PDs), lasers, and other devices. In this review provides detailed information about the synthesis methods and applications of perovskite single crystals.
Keywords: Perovskite Single Crystal; Photo-Detectors; Solar Cell; Optoelectronic Properties